2014
DOI: 10.1172/jci73066
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7a regulates pancreatic β cell function

Abstract: Dysfunctional microRNA (miRNA) networks contribute to inappropriate responses following pathological stress and are the underlying cause of several disease conditions. In pancreatic β cells, miRNAs have been largely unstudied and little is known about how specific miRNAs regulate glucose-stimulated insulin secretion (GSIS) or impact the adaptation of β cell function to metabolic stress. In this study, we determined that miR-7 is a negative regulator of GSIS in β cells. Using Mir7a2 deficient mice, we revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
299
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(336 citation statements)
references
References 64 publications
10
299
1
3
Order By: Relevance
“…Similarly, miR-7 and miR-184 have been shown to be highly enriched in the central nervous system and eye, respectively [11]. Recent studies using mouse knockouts have shown that loss of these three abundant miRNAs will increase β-cell exocytosis however it still remains unclear whether all miRNAs present in the β-cell are committed to an identical functional role and whether they perform the same function in all cell types where they are present [12] [9] [8]. For example, while miR-375 regulates exocytosis and compensatory proliferation of the β-cell, it has not been determined whether it functions in these capacities in the other neuroendocrine cell types where it is expressed [8] [13].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…Similarly, miR-7 and miR-184 have been shown to be highly enriched in the central nervous system and eye, respectively [11]. Recent studies using mouse knockouts have shown that loss of these three abundant miRNAs will increase β-cell exocytosis however it still remains unclear whether all miRNAs present in the β-cell are committed to an identical functional role and whether they perform the same function in all cell types where they are present [12] [9] [8]. For example, while miR-375 regulates exocytosis and compensatory proliferation of the β-cell, it has not been determined whether it functions in these capacities in the other neuroendocrine cell types where it is expressed [8] [13].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…Indeed, the islets of type 2 diabetic donors were found to express higher levels of miR-187, miR-187*, miR-224 and miR-589 and decreased levels of miR-7, miR-369, miR-487a, miR-655 and miR-656 (see Table 3) [13]. Similar changes in the expression of miR-187 and miR-7a were confirmed by independent research groups [25,34]. These data will need to be reproduced in additional laboratories, but if confirmed, what value will the experiments carried out in rodents have?…”
Section: Can Findings Obtained From Animal Models Of Diabetes Be Extrmentioning
confidence: 52%
“…Inhibition of miR-7 using antisense oligonucleotides in isolated adult mouse islet cells was found to activate the mechanistic target of rapamycin (mTOR) pathway and promote beta cell proliferation [24]. However, beta cell-specific MiR-7 knockout mice did not show significant differences in beta cell survival or proliferation, but displayed enhanced insulin release as a result of increased expression of key components of the exocytotic machinery, permitting an improved response to a glucose challenge [25].…”
Section: Micrornas As Regulators Of Beta Cell Differentiation and Funmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, down-regulation of miR-203, miR-210 and miR-383 resulted in an increase in apoptosis both in rat and human β-cells (109) . Altered expression in islets from diabetic donors of miR-7a, miR-187 and a cluster of miRNA in an imprinted locus on human chromosome 14q32 have also been reported and are associated with impaired insulin secretion and β-cell dysfunction (113)(114)(115) . Moreover, the expression of several miRNA was also modified in the islets of ob/ob and db/db obese mice that are deficient in leptin or leptin receptor, respectively (104,109,116,117) .…”
Section: Impact Of Nutrients On Non-coding Rna Expression In β-Cellsmentioning
confidence: 99%